استجابة اللفت الزيتي (Brassica napus L.) للتسميد بالصخر الفوسفاتي والخلط مع الكبريت في النمو وامتصاص الفوسفور (Latakia University Journal -Biological Sciences Series, 2018)
A two seasons field trial was conducted to evaluate the response of rape plant to Syrian phosphate rock (PR) and its mixture with three rates of elemental sulfur (10, 20, 50%), compared to triple super phosphate (TSP). The phosphate sources (TSP and PR) were applied at four rates (0, 400, 800, 1200 mg P/ kg soil). The results showed that rape plants were able to use applied PR in the first season irrespective of S mixing, with a relative agronomic effectiveness (RAE%) of 102%. In the second growth season the RAE of PR relative to TSP increased to 145%, and the effect of sulfur mixing with PR was more evident. The high response of rape to PR application is probably due to the released organic acids from the root system which will certainly enhance the dissolution of PR particles. بهدف دراسة مقدرة اللفت الزيتي على استخدام فوسفور الصخر الفوسفاتي (PR)  كمصدر للفوسفور، أجريت تجربة حقلية لموسمين متتالين. تضمنت الدراسة أربع معاملات هي: الشاهد، ومعاملة الـ (PR)، ومعاملة لخليط الـ PR مع الكبريت  (PRS)لتبيان أثر عملية الخلط مع الكبريت على استجابة اللفت الزيتي للصخر الفوسفاتي، ومعاملة السوبر فوسفات الثلاثي (TSP). أضيفت المصادر الفوسفاتية بثلاثة معدلات 400، 800،  1200مغP/ كغ تربة، وأضيف الكبريت وفق ثلاث نسب خلط (%10، %20، %50) نسبة للـ PR وزناً. استجاب اللفت الزيتي ولموسمين متتاليين للصخر الفوسفاتي دون الحاجة لخلطه مع الكبريت، وبلغت الفعالية الزراعية النسبية للـ PR في الموسم الأول %102، ووصلت إلى %145 في الموسم الثاني. ظهر الأثر الإيجابي لعملية الخلط مع الكبريت على استجابة اللفت الزيتي في الموسم الثاني، بينما لم يكن هذا الأثر واضحاً في الموسم الأول. ربما يعود العامل الأساس في استجابة اللفت الزيتي إلى تمتعه بخاصية طرح الأحماض العضوية في المحيط الجذري للنبات الأمر الذي يزيد من انحلال الصخر الفوسفاتي.